Extracellular vesicle DNA from human melanoma tissues contains cancer-specific mutations - Crescitelli, Rossella; Filges, Stefan; Karimi, Nasibeh; Urzì, Ornella; Alonso-Agudo, Tamara; Ståhlberg, Anders; Lötvall, Jan; Lässer, Cecilia; Olofsson Bagge, Roger (Frontiers in Cell and Developmental Biology, 2022)
Liquid biopsies are promising tools for early diagnosis and residual disease monitoring in patients with cancer, and circulating tumor DNA isolated from plasma has been extensively studied and has been shown to contain tumor-specific mutations. Extracellular vesicles (EVs) present in tumor tissues carry tumor-derived molecules such as proteins and nucleic acids, and thus EVs can potentially represent a source of cancer-specific DNA. Here we identified the presence of tumor-specific DNA mutations in EVs isolated from six human melanoma metastatic tissues and compared the results with tumor tissue DNA and plasma DNA. Tumor tissue EVs were isolated using enzymatic treatment followed by ultracentrifugation and iodixanol density cushion isolation. A panel of 34 melanoma-related genes was investigated using ultra-sensitive sequencing (SiMSen-seq). We detected mutations in six genes in the EVs (BRAF, NRAS, CDKN2A, STK19, PPP6C, and RAC), and at least one mutation was detected in all melanoma EV samples. Interestingly, the mutant allele frequency was higher in DNA isolated from tumor-derived EVs compared to total DNA extracted directly from plasma DNA, supporting the potential role of tumor EVs as future biomarkers in melanoma.